Analysis of selected percussion literature: Concerto for vibraphone and orchestra by Ney Rosauro, Surface tension by Dave Hollinden, Urban sketches for percussion trio by Lon W. Chaffin, Take five by Paul Desmond, and DT supreme by Austin Barnes - Barnes, Austin Lee (Kansas State University, 2012)
This is a report for anyone playing or teaching any one of the following pieces: Concerto for Vibraphone and Orchestra by Ney Rosauro, Surface Tension by Dave Hollinden, Urban Sketches for Percussion Trio by Lon W. Chaffin, Take Five by Paul Desmond, or DT Supreme by Austin Barnes. The repertoire is analyzed by the method given in Jan Larue’s book Guidelines for Style and Analysis. The report includes interpretive decisions, technical considerations, harmonic analysis, and form.
Keywords: Percussion; Vibraphone; Drum Set; Mallets; Music (0413); Music Education (0522)